Students' perspectives on a gender flexible school uniform policy in a higher education institution - Perez, Lawrence Bernardo (College of Home Economics, University of the Philippines Diliman, 2019)
SOGIE stands for sexual orientation, gender identity, and expression which can be expressed in various ways, and one is through clothing in individualistic ways. This premise of SOGIE is limited by the concept of school uniforms. Some students, specifically the LGBTQ, argue that a uniform policy suppresses their SOGIE. The study determined the SOGIE experiences of students of a higher education institution regarding the standard school uniform policy in terms of physical and psychosocial comfort, and their viewpoints on a gender flexible uniform policy. The respondents were determined using convenience and snowball non-probability sampling gathering total of 14 respondents participated in the focus group discussion, and 51 respondents for the online survey. The study found out that female students experience restrictions in movement due to their skirts. The study also determined cases of non-cisgender students experiencing psychosocial discomfort due to their school uniforms and dress codes prescribed to them. Most respondents are satisfied with the standard uniform policy but they also agree to a gender flexible approach for all students regardless of SOGIE. It was concluded that gender flexibility will improve the institution's reputation, and will have positive psychosocial effects on students as perceived by respondents. Based on the resilts and analysis of data, a policy brief was developed which discusses the advantages and disadvantages of both the standard and gender flexible uniform policies. The policy brief gives an overview on how gender flexible uniforms can promote a more inclusive approach towards school uniform policies. It can also be used as a baseline for legislation of bills related to SOGIE. The study recommends the institution's administration to conduct a consultation with students to comprehensively determine experiences regarding the uniform policy and viewpoints on gender flexible approach.